2018
DOI: 10.1088/1755-1315/106/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of willingness to pay for green products

Abstract: Abstract. The main purpose of this paper is to examine whether there is a positive influence of pro-environmental behavior and environmental locus of control toward the willingness to pay for green products. The data obtained by distributing online and offline questionnaires, reaching 419 respondents of 18 to ≥55 years old that have the knowledge and already bought a green product. The purposive sampling was used as the sampling technique, and the data were tested by Statistical Equation Modeling (SEM).The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…A base price of Gh¢1.80 was set with the lowest bid being Gh¢1.50 and the highest bid being Gh¢2.00. The use of CVM in previous studies (Hanemann, 1994; Freeman, 2003; Hwang et al ., 2023; Pratikto and Rikardo, 2023) is justified as it allows for the exploration of hypothetical scenarios based on the current situation, enabling inquiries into WTP. CVM facilitates direct calculations of Hicksian welfare concepts such as equivalent and compensating surplus through survey responses, without the need to derive general hypotheses or demand functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A base price of Gh¢1.80 was set with the lowest bid being Gh¢1.50 and the highest bid being Gh¢2.00. The use of CVM in previous studies (Hanemann, 1994; Freeman, 2003; Hwang et al ., 2023; Pratikto and Rikardo, 2023) is justified as it allows for the exploration of hypothetical scenarios based on the current situation, enabling inquiries into WTP. CVM facilitates direct calculations of Hicksian welfare concepts such as equivalent and compensating surplus through survey responses, without the need to derive general hypotheses or demand functions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (Hwang et al ., 2023; Freeman, 2003; Prah et al. , 2023; Pratikto and Rikardo, 2023) have highlighted the importance of utility maximization theory to model the choice of consumers. The theory indicated that an individual consumer chooses a particular product if the expected benefit is greater than cost.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding WTP, researchers found in previous literature, namely Pratiwi & Pratomo (2018) and Vicente et al (2021), placed PEB as a mediator but did not test it, only directly testing PEB on WTP. Hence, the researchers developed the model by testing PEB as a mediator between individual, organizational, and social factors on WTP.…”
Section: Em-2024-6139mentioning
confidence: 96%
“…(2018) ketika meneliti konsumen muda Indonesia menemukan bahwa walaupun konsumen mempunyai sikap positif terhadap produk ramah lingkungan, ternyata tidak berhasil mendorong mereka untuk betulbetul melakukan pembelian produknya. Walaupun konsumen Indonesia berpendapat bahwa masalah lingkungan yang dihadapi saat ini disebabkan oleh perilaku mereka (environmental locus of control), tetapi pada saat mereka harus melakukan pembelian dengan harga yang lebih mahal, ternyata konsumen tidak bersedia membeli produk hijau tersebut (Pratiwi & Pratomo, 2018).…”
Section: Pendahuluanunclassified